La variazione semantica del verbo essere nelI'italiano parlato - Alessandro, Panunzi (Firenze University Press, 2010)
The book proposes a corpus-driven study conducted on 14,000 occurrences of the verb to be in the corpus of spoken Italian C-ORAL-ROM, in the light of the main proposals for semantic interpretation of the verb. This puts to the test the very possibility of developing a study with a strong theoretical connotation on a significant mass of oral data, generally not very prone to a systematic taxonomic treatment. Thus the observable datum defines the explicandum of the linguistic reflection and the analysis of the corpus guarantees the observational adequacy in relation to the data of real production. The results proposed illustrate how the broad semantic variation in the use of the verb proves to be divided into widely comprehensive macroclasses: copular uses (attributive), identificative uses and predicative uses on locative basis. Within each of these categories we can observe principal lines of variation that are consistent and productive.